2022
DOI: 10.3389/fonc.2022.900382
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Malignant Glioma in the Elderly

Abstract: BackgroundThe median age for diagnosis of glioblastoma is 64 years and the incidence rises with increasing age to a peak at 75-84 years. As the total number of high-grade glioma patients is expected to increase with an aging population, neuro-oncological surgery faces new treatment challenges, especially regarding aggressiveness of the surgical approach and extent of resection. In the elderly, aspects like frailty and functional recovery time have to be taken into account before performing surgery.Material &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
4
2
0
Order By: Relevance
“…According to our data, resection instead of biopsy is associated with longer PFS and OS in the entire cohort. This data are concordant with the literature [ 16 , 26 , 27 ]. In our sub-group analysis, patients older than 65 years of age showed additional 12.4 months of survival, if resection instead of biopsy only was performed.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to our data, resection instead of biopsy is associated with longer PFS and OS in the entire cohort. This data are concordant with the literature [ 16 , 26 , 27 ]. In our sub-group analysis, patients older than 65 years of age showed additional 12.4 months of survival, if resection instead of biopsy only was performed.…”
Section: Discussionsupporting
confidence: 94%
“…Nowadays, biological but not chronological age in combination with frailty have more impact on the decision making in cases of malignant glioma [ 16 , 17 ]. Thus, our center generally offers aggressive tumor resection and concomitant radio-chemotherapy to elderly patients with low frailty.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the interdisciplinary treatment of older glioma patients seems to be less depending on age but must be adjusted based on the functional status of each patient. Furthermore, our findings are congruent with other studies regarding higher survival rates in patients treated with GTR compared to STR and biopsy, showing that maximum resection remains the first step of an optimal neurooncological treatment regardless of age ( Klingenschmid et al, 2022 ; Chaichana et al, 2011 ). Klingenschmid et al found that the overall survival after biopsy was shorter than after STR and GTR for elderly patients ( Klingenschmid et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our findings are congruent with other studies regarding higher survival rates in patients treated with GTR compared to STR and biopsy, showing that maximum resection remains the first step of an optimal neurooncological treatment regardless of age ( Klingenschmid et al, 2022 ; Chaichana et al, 2011 ). Klingenschmid et al found that the overall survival after biopsy was shorter than after STR and GTR for elderly patients ( Klingenschmid et al, 2022 ). These data are supported by multiple other studies, including the systematic review and meta-analysis by Almenawer et al analyzing >12,000 older patients regarding functional recovery and tumor progression and mortality or morbidity after GTR compared to biopsy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation